Clinicopathological Analysis of Uterine Allografts Including Proposed Scoring of Ischemia Reperfusion Injury and T-cell–mediated Rejection—Dallas UtErus Transplant Study: A Pilot Study. Issue 1 (January 2022) - Agarwal, Atin; Johannesson, Liza; Findeis, Sarah K.; Punar, Metin; Askar, Medhat; Ma, Tsung-Wei; Pinto, Karen; Demetris, Anthony J.; Testa, Giuliano
Abstract : Background: Uterus transplantation (UTx) enables pregnancy in infertile women. This study describes the histopathological changes of ischemia reperfusion injury and mostly acute T-cell–mediated rejection (TCMR) in UTx and proposes modification toward a working formulation grading system with associated treatments. Methods: Protocol and indication biopsies from 11 living and 2 deceased donor UTx recipients were analyzed. Serving as a control were 49 age-matched nontransplanted uteri. All posttransplant histopathological specimens were evaluated in a blinded fashion by 3 pathologists. Response to treatment was assessed by follow-up biopsies. Serial serum donor-specific antibody (DSA) responses were also recorded. Results: Changes attributed to ischemia reperfusion resolved within 2 wk of UTx in most of the patients. For TCMR grading, perivascular inflammation, focal capillary disruption, and interstitial hemorrhage were added to interface inflammation, intercellular edema, stromal inflammation, and epithelial apoptotic bodies. Of the 173 protocol biopsies, 98 were classified as negative for TCMR; 34 as indeterminate-borderline; 35 as mild; 3 as moderate; and 3 as severe, 1 of which occurred in a DSA-positive recipient and also showed microvascular injury. Corticosteroids successfully treated all moderate-to-severe TCMR episodes. Mild TCMR was treated by increasing existing baseline immunosuppression. Indeterminate-borderline episodes were not treated. Neither ischemia-reperfusion injury nor TCMR with DSA adversely affected embryo transfer. Conclusions: Relying on a modified histopathological grading system, we developed a treatment strategy resulting in resolution of TCMR and successful pregnancies. Abstract : Supplemental Digital Content is available in the text.